A COST OF ILLNESS STUDY OF TYPE 2 DIABETES MELLITUS IN MANGALORE, KARNATAKA, INDIA - Adiga, Usha; Adiga, Sachidananda (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the study was to study the cost of illness of uncomplicated and complicated type 2 diabetes mellitus. Methods: The non-interventional retrospective study was carried out in K.S. Hegde Medical Academy. Annual laboratory costs, pharmacy cost, consultation charges, hospital bed charges, and surgical/intervention costs of 340 diabetic patients were obtained from the medical record section of the hospital. Patients were divided into six groups, uncomplicated, diabetic retinopathy (DR), nephropathy, neuropathy, diabetic foot (DF), and those with ischemic heart disease (IHD) and different costs were compared. Correlation of costs with duration of the study and glycemic control were studied. Results: Uncomplicated patients had significantly lower costs (p<0.0001) compared to other groups. Patients with IHD had highest expenses (p<0.0001), followed by diabetic nephropathy (DN) and DF (p<0.0001). Cost incurred in diabetic neuropathy (DNeu) was almost the double compared to uncomplicated group, but annual medical cost (AMC) was minimum among other diabetic complications. DR had higher expenses compared to DNeu. The similar pattern of distribution was observed in other individual costs. A positive correlation was observed between the costs incurred and duration of diabetes, a negative correlation between the glycemic status and cost incurred. Cost incurred was double when compared to that of previous decade. Conclusion: The total AMC is significantly higher in complicated diabetic patients as compared to those without complications. Diabetic patients with IHD had the highest expenses, followed by DN, DF, DR, and DNeu which was least expensive.